PENTINGNYA ASESMEN AUTENTIK DAN ALTERNATIF DALAM PEMBELAJARAN BIOLOGI - Karmana, I Wayan (Bioscientist : Jurnal Ilmiah Biologi, 2013)
The change of learning paradigm today from teacher centered to student centered has implication to the assessment system (assessment). Assessment not only relies on tests but also refers to performance in the form of authentic assessment and alternative assessment that is better able to dig information holistically about students' ability either affective, cognitive, or psychomotor aspects. Therefore, it is necessary to understand and implement it in the assessment of biology learning process.